Yield-based selection indices for drought tolerance evaluation in selected bottle gourd [Lagenaria siceraria (Molina) Standl.] landraces. (2nd January 2017) - Mashilo, Jacob; Shimelis, Hussein; Odindo, Alfred
ABSTRACT: Bottle gourd is an important crop in arid and semi-arid tropics where recurrent drought is the major constraint to crop production. Identification of drought-tolerant bottle gourd genotypes is fundamental to enhance productivity and for effective breeding and conservation. The objective of this study was to determine drought tolerance of a diverse set of bottle gourd landraces and to identify promising genotypes for direct production or breeding. A field study was conducted using a 12 × 2 factorial experiment involving 12 bottle gourd landraces under drought-stressed (DS) and non-stressed (NS) conditions. Significant differences were observed among bottle gourd landraces with respect to fruit yield under DS and NS conditions. The mean fruit yield under DS and NS conditions was 8.75 and 22.4 t ha −1, respectively. Drought stress reduced fruit yield by 62%. Correlation and principal component analyses revealed the significance of yield-based indices of drought tolerance, such as tolerance index, geometric mean productivity, stress tolerance, mean productivity, yield index and harmonic mean, which allowed discrimination of drought-tolerant bottle gourd landraces. Such landraces as BG-79, BG-31, BG-67, BG-52, BG-78 and GC were identified useful for drought tolerance breeding or rootstock development programs.